PENERAPAN NILAI NILAI PANCASILA SEBAGAI LANDASAN ILMU KEPERAWATAN DALAM PELAYANAN KESEHATAN DI INDONESIA - Hidayah, Miftahul (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Pancasila as the basis of the state and the way of life of the Indonesian people has an important role in forming the moral and ethical values that underlie various aspects of life, including health services and nursing science. This article discusses the application of Pancasila values in the context of nursing science as a basis for ethics and professionalism in providing dignified, fair and humane health services. Each Pancasila principle is analyzed to show its relevance in nursing practice, such as respect for human rights, justice in health services, and the spirit of mutual cooperation in the medical community. This research also highlights the challenges and strategies in integrating Pancasila values into nursing education and practice in Indonesia. It is hoped that the results of this discussion can become a reference for improving the quality of health services based on national values, strengthening relationships between health workers and patients, and building a more inclusive and humane health system.